Buttressing impact on diameter estimation in plantation teak (Tectona grandis L.f.) sample trees in northern Thailand - Andrew J. Warner, Andrew J.; Jamroenprucksa, Monton; Puangchit, Ladawan (Agriculture and Natural Resources, 2017)
Buttressing consists of ground-upward deformations from the circular cross section of a tree and can be quite pronounced in tropical species, thus making the measurement of lower diameters in older trees especially problematical in collecting accurate sample tree data. A technique to correct for buttress distortion of diameter estimates from girth tape measurement was applied using photographic images of cross sections at known lower bole heights on 331 plantation teak sample trees in eight plantations over four provinces in northern Thailand. Image scaling and image correction for distortion were used to obtain an equivalent diameter based on the actual digitized sectional area and standard geometry. The estimates of diameters over buttressing exceeded equivalent sectional area diameter estimates by more than a nominated 3% difference for at least one measuring height in the lower bole on 73% of the trees measured. The results of the t-test analysis indicated that the two sets of diameters were highly significantly (p < 0.001) different with the data measured using the girth tape overestimating the actual buttressed sectional area based on the sectional analysis. The study indicated that pronounced buttressing is common, especially in the lower bole of plantation teak trees and correction is essential where such sample tree measurements are to be used in taper modeling to avoid introducing a potentially large overestimation bias into the model.